2021
DOI: 10.1001/jamapsychiatry.2021.0638
|View full text |Cite
|
Sign up to set email alerts
|

Association of Structural Magnetic Resonance Imaging Measures With Psychosis Onset in Individuals at Clinical High Risk for Developing Psychosis

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 81 publications
13
65
0
Order By: Relevance
“…Longitudinal data and case-control meta-analysis have shown that the development of psychosis in high-risk adolescents is associated with progressive loss of cortical thickness in several areas of the association cortex [18,72]. Of note, the areas implicated in these studies overlap considerably with those showing increased cortical thickness in early childhood and more pronounced cortical thinning in adolescents with higher PRS-SCZ in the current study.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Longitudinal data and case-control meta-analysis have shown that the development of psychosis in high-risk adolescents is associated with progressive loss of cortical thickness in several areas of the association cortex [18,72]. Of note, the areas implicated in these studies overlap considerably with those showing increased cortical thickness in early childhood and more pronounced cortical thinning in adolescents with higher PRS-SCZ in the current study.…”
Section: Discussionmentioning
confidence: 58%
“…We observed that the PRS-SCZ effects on cortical thickness appear to be transient and disappear with cortical maturation in typically developing children and adolescents; however, we presume that they may persist or worsen in the presence of other biological and environmental risk factors. Several longitudinal and case-control studies have shown that the development of psychosis in high-risk adolescents is associated with progressive loss of cortical thickness in several areas of association cortex (Pantelis et al ., 2003; Cannon et al ., 2015; ENIGMA Clinical High Risk for Psychosis Working Group et al ., 2021). Of note, the areas implicated in these studies overlap considerably with those showing increased cortical thickness with higher PRS-SZ here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant impairments in receptive language scores and microstructural changes in the arcuate fasciculus, a language-related white matter tract connecting the inferior frontal gyrus, were previously reported in this cohort of adolescents with PEs at 11–13 years ( Blanchard et al, 2010 , Dooley et al, 2020 ). Accelerated frontal lobe cortical thinning has been observed in adolescents who developed depressive symptoms ( Bos et al, 2018 ), in externalising behaviours in adolescents ( Tanzer et al, 2020 ) and in adolescents at chronic high risk of psychosis ( Cannon et al, 2015 , ENIGMA Clinical High Risk for Psychosis Working Group et al, 2021 , Jung et al, 2011 ). Other robust frontal cortical regions classifying the 18–20 year old group included the left superior frontal cortex and left orbitofrontal cortex.…”
Section: Discussionmentioning
confidence: 99%